Adapting to Innovation: The changes of learners' Perceptions about the role of Generative AI in Chinese Language Learning within Irish Higher Education - Wang, Hongfei (My University, 2024)
This research delves into ChatGPT's integration as a Technology-Enhanced Language Learning (TELL) instrument in teaching Chinese as an Additional Language (CAL) in Irish Higher Education. Utilizing qualitative methods, this study draws on interviews with CAL learners from a master’s program across two academic cohorts to examine shifts in perceptions, feedback, and engagement with ChatGPT in CAL. The first group from the 2022/23 academic year encountered ChatGPT shortly after its release, experiencing a mix of novelty and scepticism regarding the potential of AI in language education. In contrast, the 2023/24 cohort interacted with ChatGPT against a backdrop of wider acceptance and utility, reflecting a significant shift towards viewing it as a standard educational tool, characterized by increased comfort and reliance among students. A comparative analysis of these cohorts reveals an evolving appreciation for ChatGPT as an invaluable educational resource, providing instantaneous feedback and support. However, this study also uncovers lingering concerns over linguistic accuracy and language control in Chinese, highlighting the need for continued improvement. Through a qualitative lens, this investigation sheds light on changing learners’ attitudes towards Generative AI in language learning, offering insights for future research aimed at enhancing Generative AI tools like ChatGPT to optimize learning outcomes and address existing limitations. This work contributes to the broader understanding of AI's evolving role in facilitating effective Chinese language education.
AI IN EDUCATION / (DIS)EMBODIED INTERACTIONS
Keywords: ChatGPT, TELL, Generative AI, CAL, language learning, educational technology; Applied Linguistics; Education and minority language; Language Acquisition and Development; Second language acquisition; Technology and communication